The Importance and Prevention of Mastitis in Mothers - GÜL, ASİYE (My University, 2019)
Aim: This review emphasizes the incidence of mastitis in breastfeeding mothers and what needs to be done to prevent mastitis. Introduction: Mastitis, inflammation of the breast, refers to the inflammatory disease o f the breast. Mastitis is classified as lactating (puerperal), non-lactating and breast abscess. Lactational mastitis is the most common mastitis. Lactational mastitis is seen in 3-33%. It is more common in the first 12 weeks of breastfeeding. Most breast abscess develops as a complication of lactational mastitis. Milk stasis and infection are two main causes. Staphylococcus aureus is the most common causative agent for mastitis. Other organisms include streptococcus and S. epidermidis. Patients with recurrent breast abscess have an increased incidence of mixed flora, including anaerobic organisms. Breast pain is the primary symptom of mastitis. Other symptoms; vomiting with general flu-like symptoms such as high fever, weakness, muscle pain, sweating, and headache. In addition to physiological problems, such as depression, anxiety, and helplessness develop. This affects daily life activities and causes lifestyle changes. Providing the right breastfeeding milk flow is the main principle of treatment. Breastfeeding is not harmful to the baby, it is also the ideal way to drain the milk. Lack of education on postpartum breast care, reduction of local hygiene conditions, encouraging the mother to breastfeed, and correcting the newborns should be correctly positioned. Conclusion: The incidence of mastitis can be reduced by informing the mothers and changing their attitudes in a positive way.
Keywords: Lactation; Mastitis; Mother; Emzirme; Meme İltihabı; Anne